Módulo temático: contribuição para a formação continuada de professores de ciências - Rocha, Thaís Rios da (2018)
As it is very important to offer professional training courses for primary school teachers, this paper aims to investigate if the development of thematic modules in a continuing education course contributes to the development of science teachers in basic education. In order to respond to this questioning, this research was structured in five stages of action research and the data were analyzed through text discourse analysis, elaborating a priori and emerging categories. Prior to the implementation of the continuing education course, a bibliographical survey was carried out in national and international period about continuous training for science teachers from 2006 to 2016. 68 publications were analyzed and just 13 were courses for science teachers. Among them, only one publication was related to the category "formative and reflective practices". From this analysis we structured the meetings of the continuing education course in order to dedicate moments of reflection about teaching work, problems in school actives and reports about situations experienced by teachers. The implementation of continuing education course there were 10 teachers in the school in monthly meetings from May to November in 2017. During the course different issues were approached like the use of thematic in sciences teaching, 5W2H method, bloom taxonomy, among others. The teachers worked together to produce thematic modules proposed by this paper as a teaching methodology to be used in basic education. In the year following the implementation of the continuing education course, one of the participating teachers applied the thematic module in their school of work. Soon after, we conducted a semi-structured interview and the feedback was sent to all participants. It can be evidenced from the results of this research that the continuous training course contributed to the development of teachers, as it enabled new learning related to the use of different teaching methodologies and the exchange of experiences among teachers. From the analysis of classroom diaries produced by teachers, we find evidence of a process of teacher reflection, being noticed an evolution mainly in the writing of two diaries, which began with reports of the referential type and, with the passing of the written ones, carried out reflections of the referential/expressive type. Regarding the thematic modules elaborated during the course of continuous training, 4 of the 5 groups performed thematic modules classified as "well structured" and only one group as "structured". In the final evaluation of the continuing education course, teachers also reported on the feasibility of thematic module used in teaching of sciences at school, because the planning is made according to hierarchical levels of bloom taxonomy, which makes possible to monitor students’ learning during the 8 steps.